2023
DOI: 10.3390/plants12051130
|View full text |Cite
|
Sign up to set email alerts
|

Two Newly Identified Colletotrichum Species Associated with Mango Anthracnose in Central Thailand

Abstract: Anthracnose caused by Colletotrichum spp. is one of the major problems in mango production worldwide, including Thailand. All mango cultivars are susceptible, but Nam Dok Mai See Thong (NDMST) is the most vulnerable. Through a single spore isolation method, a total of 37 isolates of Colletotrichum spp. were obtained from NDMST showing anthracnose symptoms. Identification was performed using a combination of morphology characteristics, Koch’s postulates, and phylogenetic analysis. The pathogenicity assay and Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Similar to other studies, the MLSA demonstrated better resolution at the species level compared to individual gene analyses. For instance, a study by Rattanakreetakul et al [23] compared two phylogenetic trees for Colletotrichum species. The MLSA approach, which used four loci (ITS, TUB2, ACT, and CHS-1), provided more accurate identification, distinguishing them into C. acutatum, C. gloeosporioides, C. asianum, and C. siamense, compared to using only two loci (ITS and TUB2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other studies, the MLSA demonstrated better resolution at the species level compared to individual gene analyses. For instance, a study by Rattanakreetakul et al [23] compared two phylogenetic trees for Colletotrichum species. The MLSA approach, which used four loci (ITS, TUB2, ACT, and CHS-1), provided more accurate identification, distinguishing them into C. acutatum, C. gloeosporioides, C. asianum, and C. siamense, compared to using only two loci (ITS and TUB2).…”
Section: Discussionmentioning
confidence: 99%
“…For molecular identification of fungal isolates, the total genomic DNA was extracted from fresh mycelial on spezieller nährstoffarmer broth (SNB) for 5 days following the protocol described by Zimand et al [44] and Rattanakreetakul et al [23]. The extracted DNA samples were then stored at −20 • C for further analysis.…”
Section: Dna Extraction and Molecular Identificationmentioning
confidence: 99%